Preparation method of high-uniform manganese-doped BSPT-based piezoelectric ceramic
Patent Information
- Application Number
- CN202610950410.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-09-11
AI Technical Summary
然而,现有锰掺杂BSPT的制备工艺仍存在显著弊端:行业内普遍采用所有原料统一混料共同预烧的方式,受限于A位Bi、Pb易高温挥发的特性,整体预烧结温度不宜过高
1、本发明通过将B位氧化物单独进行高温预烧,既能显著提高B位离子扩散速率,实现Sc、Ti、Mn组分均匀混合,又能在高温低氧环境下稳定获得二价锰离子,使其均匀分布于B位并形成有效缺陷偶极子,增强电畴钉扎效果;
Smart Images

Figure CN122725833A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of piezoelectric ceramics technology and relates to a method for preparing highly uniform manganese-doped BSPT-based piezoelectric ceramics. Background Technology
[0002] In aerospace, oil and gas exploration, and high-end automotive electronics, the demand for high-temperature, high-power piezoelectric devices continues to rise, making high-performance, high-temperature-resistant piezoelectric ceramics a core material. Traditional piezoelectric ceramic systems generally suffer from insufficient high-temperature resistance, with long-term service temperatures typically not exceeding 300°C. They also generally exhibit low mechanical quality factors. Under high-frequency vibration and high-temperature operating conditions, these materials are prone to severe heat generation, rapid performance degradation, and poor structural stability, making them unsuitable for extreme operating conditions and long-term reliable use. Therefore, developing novel piezoelectric ceramic materials with high mechanical quality factors, wide temperature range stability, and high reliability is a key research focus urgently needed in the field of piezoelectric functional materials.
[0003] Bismuth scandium lead titanate (BSPT) ceramics possess excellent piezoelectric response and good high-temperature performance potential, making them a highly valuable candidate material for high-temperature functional ceramics. However, this system generally suffers from a low mechanical quality factor and insufficient structural stability under high-temperature conditions. Currently, Mn doping is a common modification method to improve the mechanical quality factor of piezoelectric ceramics and is often used to optimize BSPT ceramics to improve their mechanical losses and high-temperature service reliability. However, existing manganese-doped BSPT preparation processes still have significant drawbacks: the industry generally adopts a method of uniformly mixing all raw materials and pre-firing them together. Due to the high-temperature volatilization characteristics of Bi and Pb at the A-site, the overall pre-sintering temperature should not be too high. However, low-temperature pre-sintering significantly inhibits the diffusion ability of scandium ions, resulting in uneven mixing of B-site components and poor dispersion of manganese doping; at the same time, under low-temperature oxidizing atmosphere, manganese mainly exists in trivalent and tetravalent forms, making it difficult to stably generate divalent manganese, failing to form effective defect dipoles, and resulting in weak domain pinning. This results in the inability to fully realize the modification effect of manganese doping, limited improvement in the mechanical quality factor of the material, and poor high-temperature stability, which seriously restricts the practical application and large-scale production of BSPT piezoelectric ceramics.
[0004] Based on this, the present invention is proposed. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention aims to provide a method for preparing highly uniform manganese-doped BSPT-based piezoelectric ceramics, following the chemical formula 0.34BiScO3-0.66Pb(Ti 0.645 Mn 0.015The process involves ball milling, drying, and sieving Sc2O3, TiO2, and MnO2, followed by calcination at 1150℃ to obtain B-site precursor powder. PbO and Bi2O3 are then added, followed by ball milling, drying, and pre-calcination. This is followed by secondary ball milling, PVA granulation, pressing, debinding, and sintering. Finally, the powder is polished, gold-sprayed, polarized, and aged to obtain highly uniform manganese-doped BSPT-based piezoelectric ceramics. This invention achieves atomic-level uniform mixing of Sc, Ti, and Mn through high-temperature calcination of B-site oxides, and ensures that Mn is in a low valence state (MnO2). 2+ Stable solid solution at the B site forms an effective defect dipole, significantly improving the mechanical quality factor Q. m It boasts high reliability during high-temperature service, and its process is stable and controllable, making it suitable for industrial production.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing highly uniform manganese-doped BSPT-based piezoelectric ceramics, comprising the following steps in sequence: S1, according to the chemical formula 0.34BiScO3-0.66Pb(Ti 0.645 Mn 0.015 O3 is used for ingredient preparation; S2. Add Sc2O3, TiO2, and MnO2 together into a ball mill jar for ball milling; S3. Place the ball-milled slurry in an oven to dry; grind the dried powder in a mortar and pestle, and pass it through a 100-mesh sieve to obtain a mixture; S4. The mixture is placed in a crucible and calcined in a muffle furnace to obtain B-site precursor powder. S5. Add PbO and Bi2O3 to the B-site precursor powder, ball mill at 200 r / min for 24 h, dry in an oven after ball milling, grind and pass through a 100-mesh sieve and then pre-calcine in a muffle furnace. S6. Put the pre-calcined powder back into the ball mill jar and ball mill it again at 200 r / min for 24 h. After drying, add PVA binder, grind it evenly, and pass it through a 100-mesh sieve to obtain granulated powder. S7. Place the granulated powder in a mold with a diameter of 12.85 mm, hold it under a pressure of 6 MPa for 2 min, press it into a ceramic green body, and then sinter it in a muffle furnace to obtain a dense ceramic sheet. S8. Polish the ceramic sheet with 800-grit sandpaper until both sides are flat, and spray gold on both sides for 5 min. DC polarize at 140 ℃ and 6 kV / mm for 25 min. Place the polarized sample in an oven and age at 200 ℃ for 12 h to obtain highly uniform manganese-doped BSPT-based piezoelectric ceramic.
[0007] As a limitation of the present invention, in step S2, the ball milling medium is anhydrous ethanol, the ball milling rate is 200 r / min, and the time is 24 h.
[0008] As another limitation of the present invention, in step S3, the drying temperature is 110-120 ℃ and the time is 120-140 min.
[0009] As a third limitation of the present invention, in step S4, the calcination process is carried out according to the following procedure: (a) During the heating stage, the temperature was increased from 30 ℃ to 1150 ℃ at a heating rate of 4 ℃ / min, and held for 240 min; (b) During the cooling phase, the temperature is reduced from 1150 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min.
[0010] As a fourth limitation of the present invention, in step S5, the pre-firing process is as follows: first, the temperature is increased from 30°C to 730-750°C at a heating rate of 4°C / min, and held for 180 min; then, the temperature is decreased from 730-750°C to 30°C at a cooling rate of 4°C / min.
[0011] As a fifth limitation of the present invention, in step S6, the mass of the PVA binder added is 7 wt.% of the mass of the pre-fired powder.
[0012] As one of the six limitations of the present invention, in step S7, the sintering process is performed according to the following procedure: (1) In the first heating stage, the temperature was increased from room temperature to 550 ℃ at a heating rate of 4 ℃ / min, and the temperature was maintained for 120 min for debinding. (2) In the second heating stage, the temperature is increased from 550 ℃ to 900 ℃ at a heating rate of 4 ℃ / min; (3) In the second heating stage, the temperature is increased from 900 ℃ to 1100 ℃ at a heating rate of 2 ℃ / min, and held for 120 min; (4) During the cooling stage, the temperature is reduced from 1100 ℃ to 800 ℃ at a cooling rate of 10 ℃ / min, and held for 180 min. Then, the temperature is cooled to room temperature with the furnace.
[0013] In the traditional one-step process, Bi₂O₃ (melting point 817℃) and PbO (melting point 886℃) readily form a liquid phase at the calcination temperature, preferentially reacting with TiO₂ and Sc₂O₃ to form a perovskite phase. This results in MnO₂ being pushed to the grain boundary region, leading to microscopic segregation of Mn elements. This invention addresses this by separately calcining the B-site oxide at 1150℃ in a solid-phase reaction environment free from liquid phase interference. This allows Mn ions to fully diffuse and react with Sc₂O₃. 3+ Ti4+ A composite oxide with atomically homogeneous mixture is formed. When PbO and Bi2O3 are subsequently added, Mn is already firmly dissolved in the B-site framework, avoiding secondary segregation in the low-temperature liquid phase. This allows Mn to achieve near-atomic-level uniform distribution in the ceramic matrix, reducing local compositional fluctuations, suppressing the formation of Mn-rich second phases at grain boundaries, and improving breakdown field strength. It also improves the consistency of material properties and batch stability.
[0014] In this invention, Mn ions exist in a divalent form, which allows for better pinning of domains: MnO2 undergoes the following chemical reaction at high temperatures: MnO2→500℃→Mn2O3→900℃→Mn3O4→1100℃→MnO.
[0015] It can be seen that Mn can only become a divalent ion at temperatures above 1100℃. In this invention, the B-site precursor is subjected to high-temperature calcination at 1150℃ for 240 minutes, allowing for complete thermal decomposition of MnO2, releasing oxygen, and reducing Mn to a lower valence state (MnO2). 2+ Mn is primarily dissolved and stably dissolved in the B-site lattice formed by Sc / Ti. The subsequent pre-firing temperature is only 730-750℃, far below the activation threshold required for Mn re-oxidation, ensuring that Mn... 2+ The valence state is largely retained during subsequent synthesis and sintering processes.
[0016] low-valence Mn 2+ Regardless of replacing Ti 4+ Or Sc 3+ Effective acceptor doping can be formed at any time, inducing the generation of oxygen vacancies according to the principle of electroneutrality: Mn 2+ →Ti 4+ +V O·· .
[0017] Oxygen vacancies and Mn 2+ The formation of defect dipoles pins domain wall motion, significantly reducing dielectric loss (tan δ). This improves the mechanical quality factor Qm, making the material more suitable for applications such as high-power resonators and ultrasonic transducers.
[0018] The above-mentioned technical solution of the present invention is a whole in which each step is closely related and mutually influential, and together they determine the morphological characteristics and performance of the product.
[0019] The above technical solution has the following advantages or beneficial effects: 1. This invention significantly improves the diffusion rate of B-site ions by pre-calcining the B-site oxides at high temperature, achieving uniform mixing of Sc, Ti, and Mn components, and stably obtaining divalent manganese ions in a high-temperature and low-oxygen environment, so that they are uniformly distributed at the B-site and form effective defect dipoles, thereby enhancing the domain pinning effect. 2. This invention solves the problems of uneven ion diffusion and difficulty in controlling the manganese valence state in traditional co-firing processes. The prepared BSPT ceramics have a uniform microstructure, stable performance, significantly improved mechanical quality factor, and significantly improved high-temperature service reliability. 3. The process of this invention is stable and controllable, suitable for mass production. The segmented preparation process is clear, the parameters are easy to control, and the repeatability is good. No special equipment or atmosphere is required, and it can be directly used for industrial production.
[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. Attached Figure Description
[0021] Figure 1 The XRD patterns of the piezoelectric ceramics prepared in Example 1 and Comparative Examples 1-2 of this invention are shown below. Figure 2 This is a comparison chart showing the mechanical quality factor Q values of the piezoelectric ceramics prepared in Embodiment 1 and Comparative Examples 1-2 of the present invention. Detailed Implementation
[0022] The following embodiments are merely some, not all, of the embodiments of the present invention. Therefore, the detailed descriptions of the embodiments provided below are not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0023] In this invention, unless otherwise specified, all equipment and raw materials are commercially available or commonly used in the industry. The methods described in the following embodiments are conventional methods in the art, unless otherwise specified.
[0024] Example 1
[0025] This embodiment describes a method for preparing highly uniform manganese-doped BSPT-based piezoelectric ceramics. The preparation process and steps are as follows: S1, according to the chemical formula 0.34BiScO3-0.66Pb(Ti 0.645 Mn 0.015 O3 is used for ingredient preparation; S2. Add Sc2O3, TiO2 and MnO2 together into a ball milling jar, use anhydrous ethanol as the ball milling medium, and ball mill at 200 r / min for 24 h. S3. Place the ball-milled slurry in an oven and dry it at 110 ℃ for 140 min; grind the dried powder in a mortar and crush it, and pass it through a 100-mesh sieve to obtain a mixture; S4. Load the mixture into a crucible and place the crucible in a muffle furnace. First, heat the mixture from 30 ℃ to 1150 ℃ at a heating rate of 4 ℃ / min and hold it for 240 min. After holding, cool the mixture from 1150 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min to obtain the B-site precursor powder. S5. Add PbO and Bi2O3 to the B-site precursor powder, ball mill at 200 r / min for 24 h, place in an oven and dry at 110 ℃ for 120 min, grind and pass through a 100-mesh sieve, then place in a muffle furnace for pre-calcination. During pre-calcination, first heat from 30 ℃ to 730 ℃ at a heating rate of 4 ℃ / min and hold for 180 min; then cool from 730 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min. S6. Place the pre-calcined powder back into the ball mill jar and ball mill it again at 200 r / min for 24 h. After drying, add 7 wt.% of PVA binder to the pre-calcined powder, grind it evenly, and pass it through a 100-mesh sieve to obtain granulated powder. S7. Place 0.7 g of granulated powder in a mold with a diameter of 12.85 mm and press it under a pressure of 6 MPa for 2 min to form a ceramic green body. Then place it in a muffle furnace and first heat it from room temperature to 550 ℃ at a heating rate of 4 ℃ / min and hold it for 120 min to remove the binder. Then heat it from 550 ℃ to 900 ℃ at a heating rate of 4 ℃ / min, then heat it from 900 ℃ to 1100 ℃ at a heating rate of 2 ℃ / min and hold it for 120 min. Finally, cool it from 1100 ℃ to 800 ℃ at a cooling rate of 10 ℃ / min and hold it for 180 min. Then cool it to room temperature with the furnace to obtain a dense ceramic sheet. S8. Polish the ceramic sheet with 800-grit sandpaper until both sides are flat, and spray gold on both sides for 5 min. DC polarize at 140 ℃ and 6 kV / mm for 25 min. Place the polarized sample in an oven and age at 200 ℃ for 12 h to obtain highly uniform manganese-doped BSPT-based piezoelectric ceramic.
[0026] Example 2
[0027] This embodiment describes a method for preparing highly uniform manganese-doped BSPT-based piezoelectric ceramics. The preparation process and steps are as follows: S1, according to the chemical formula 0.34BiScO3-0.66Pb(Ti 0.645 Mn 0.015 O3 is used for ingredient preparation; S2. Add Sc2O3, TiO2 and MnO2 together into a ball milling jar, use anhydrous ethanol as the ball milling medium, and ball mill at 200 r / min for 24 h. S3. Place the ball-milled slurry in an oven and dry it at 115 ℃ for 130 min; grind the dried powder in a mortar and crush it, and pass it through a 100-mesh sieve to obtain a mixture; S4. Load the mixture into a crucible and place the crucible in a muffle furnace. First, heat the mixture from 30 ℃ to 1150 ℃ at a heating rate of 4 ℃ / min and hold it for 240 min. After holding, cool the mixture from 1150 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min to obtain the B-site precursor powder. S5. Add PbO and Bi2O3 to the B-site precursor powder, ball mill at 200 r / min for 24 h, place in an oven and dry at 110 ℃ for 120 min, grind and pass through a 100-mesh sieve, then place in a muffle furnace for pre-calcination. During pre-calcination, first heat from 30 ℃ to 740 ℃ at a heating rate of 4 ℃ / min and hold for 180 min; then cool from 740 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min. S6. Put the pre-calcined powder back into the ball mill jar and ball mill it again at 200 r / min for 24 h. After drying, add 7 wt.% of PVA binder to the pre-calcined powder, grind it evenly, and pass it through a 100-mesh sieve to obtain granulated powder. S7. Place 0.7 g of granulated powder in a mold with a diameter of 12.85 mm and press it under a pressure of 6 MPa for 2 min to form a ceramic green body. Then place it in a muffle furnace and first heat it from room temperature to 550 ℃ at a heating rate of 4 ℃ / min and hold it for 120 min to remove the binder. Then heat it from 550 ℃ to 900 ℃ at a heating rate of 4 ℃ / min, then heat it from 900 ℃ to 1100 ℃ at a heating rate of 2 ℃ / min and hold it for 120 min. Finally, cool it from 1100 ℃ to 800 ℃ at a cooling rate of 10 ℃ / min and hold it for 180 min. Then cool it to room temperature with the furnace to obtain a dense ceramic sheet. S8. Polish the ceramic sheet with 800-grit sandpaper until both sides are flat, and spray gold on both sides for 5 min. DC polarize at 140 ℃ and 6 kV / mm for 25 min. Place the polarized sample in an oven and age at 200 ℃ for 12 h to obtain highly uniform manganese-doped BSPT-based piezoelectric ceramic.
[0028] Example 3
[0029] This embodiment describes a method for preparing highly uniform manganese-doped BSPT-based piezoelectric ceramics. The preparation process and steps are as follows: S1, according to the chemical formula 0.34BiScO3-0.66Pb(Ti 0.645 Mn 0.015O3 is used for ingredient preparation; S2. Add Sc2O3, TiO2 and MnO2 together into a ball milling jar, use anhydrous ethanol as the ball milling medium, and ball mill at 200 r / min for 24 h. S3. Place the ball-milled slurry in an oven and dry it at 120 ℃ for 120 min; grind and crush the dried powder in a mortar and pestle, and pass it through a 100-mesh sieve to obtain a mixture; S4. Load the mixture into a crucible and place the crucible in a muffle furnace. First, heat the mixture from 30 ℃ to 1150 ℃ at a heating rate of 4 ℃ / min and hold it for 240 min. After holding, cool the mixture from 1150 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min to obtain the B-site precursor powder. S5. Add PbO and Bi2O3 to the B-site precursor powder, ball mill at 200 r / min for 24 h, place in an oven and dry at 110 ℃ for 120 min, grind and pass through a 100-mesh sieve, then place in a muffle furnace for pre-calcination. During pre-calcination, first heat from 30 ℃ to 750 ℃ at a heating rate of 4 ℃ / min and hold for 180 min; then cool from 750 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min. S6. Put the pre-calcined powder back into the ball mill jar and ball mill it again at 200 r / min for 24 h. After drying, add 7 wt.% of PVA binder to the pre-calcined powder, grind it evenly, and pass it through a 100-mesh sieve to obtain granulated powder. S7. Place 0.7 g of granulated powder in a mold with a diameter of 12.85 mm and press it under a pressure of 6 MPa for 2 min to form a ceramic green body. Then place it in a muffle furnace and first heat it from room temperature to 550 ℃ at a heating rate of 4 ℃ / min and hold it for 120 min to remove the binder. Then heat it from 550 ℃ to 900 ℃ at a heating rate of 4 ℃ / min, then heat it from 900 ℃ to 1100 ℃ at a heating rate of 2 ℃ / min and hold it for 120 min. Finally, cool it from 1100 ℃ to 800 ℃ at a cooling rate of 10 ℃ / min and hold it for 180 min. Then cool it to room temperature with the furnace to obtain a dense ceramic sheet. S8. Polish the ceramic sheet with 800-grit sandpaper until both sides are flat, and spray gold on both sides for 5 min. DC polarize at 140 ℃ and 6 kV / mm for 25 min. Place the polarized sample in an oven and age at 200 ℃ for 12 h to obtain highly uniform manganese-doped BSPT-based piezoelectric ceramic.
[0030] Comparative Example To investigate the influence of different preparation steps on the performance of the product of this invention, the following comparative experiments were conducted. Different piezoelectric ceramics were prepared in the following comparative examples, as detailed below: Comparative Example 1 This comparative example prepares a piezoelectric ceramic. The preparation process is similar to that of Example 1, except that steps S1-S4 are not performed. That is, Sc2O3, TiO2, MnO2 and PbO, Bi2O3 are directly ball-milled together, and then the same subsequent steps as in Example 1 are performed.
[0031] Comparative Example 2 This comparative example prepares a piezoelectric ceramic. The preparation process is similar to that of Example 1, except that in step S4, the sintering temperature is changed from 1150 ℃ to 950 ℃.
[0032] Performance testing The piezoelectric ceramics prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to a series of tests, as detailed below: like Figure 1 The figures show the XRD patterns of the piezoelectric ceramics prepared in Example 1 and Comparative Examples 1-2 of this invention. As can be seen from the figures, the ceramic prepared by the B-site precursor process under high-temperature calcination (Example 1) has a higher peak value and a sharper peak shape, i.e., a smaller full width at half maximum (FWHM). This indicates that the ceramic has higher crystallinity and better uniformity of lattice distortion, i.e., a more uniform composition. The peak value and FWHM of Example 1 are significantly improved compared to Comparative Example 2, indicating that a calcination temperature of 1150℃ is more suitable. Furthermore, compared to Comparative Example 1, Example 1 shows a higher peak value at 29℃. ° 43 ° 47 ° The phase structure is purer.
[0033] contrast Figure 1 The diffraction peaks in Example 1, compared to the two comparative examples, are shifted to lower angles at mid-to-high angles. According to Bragg's equation... The results showed that lattice expansion existed in the examples, which is because the radius of the low-valence manganese ion is much larger than that of the high-valence Mn ion. 2+ (0.830Å) > Mn 3+ (0.645Å) > Mn 4+ (0.530 Å) indicates that there are more divalent manganese ions with larger radii at the B site in Example 1, which proves that the preparation process can better adjust the valence state and distribution uniformity of manganese ions.
[0034] like Figure 2The figure shows a comparison of the mechanical quality factor Q of the piezoelectric ceramics prepared in Example 1 and Comparative Examples 1-2 of this invention. As can be seen from the figure, Example 1 shows a significant improvement compared to Comparative Examples 1 and 2, indicating that the high-temperature pre-calcination of the B-site precursor process more easily forms uniformly distributed defect dipoles and better pinns domain walls. However, Comparative Example 1, due to the absence of a separate calcination process for the B-site oxide of this invention, suffers from uneven mixing of B-site ions, leading to enrichment of titanium or scandium in some areas, ultimately resulting in a lower Q. m The value is relatively small; because the temperature during the individual calcination process of the B-site oxide in Comparative Example 2 is lower than that of this invention, the uniformity of scandium ion distribution is limited, which in turn leads to Q... m Limited improvement.
[0035] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing highly uniform manganese-doped BSPT-based piezoelectric ceramics, characterized in that, Follow these steps in sequence: S1, according to the chemical formula 0.34BiScO3-0.66Pb(Ti 0.645 Mn 0.015 O3 is used for ingredient preparation; S2. Add Sc2O3, TiO2, and MnO2 together into a ball mill jar for ball milling; S3. Place the ball-milled slurry in an oven to dry; grind the dried powder in a mortar and pestle, and pass it through a 100-mesh sieve to obtain a mixture; S4. The mixture is placed in a crucible and calcined in a muffle furnace to obtain B-site precursor powder. S5. Add PbO and Bi2O3 to the B-site precursor powder, ball mill at 200 r / min for 24 h, dry in an oven after ball milling, grind and pass through a 100-mesh sieve and then pre-calcine in a muffle furnace. S6. Put the pre-calcined powder back into the ball mill jar and ball mill it again at 200 r / min for 24 h. After drying, add PVA binder, grind it evenly, and pass it through a 100-mesh sieve to obtain granulated powder. S7. Place the granulated powder in a mold with a diameter of 12.85 mm, hold it under a pressure of 6 MPa for 2 min, press it into a ceramic green body, and then sinter it in a muffle furnace to obtain a dense ceramic sheet. S8. Polish the ceramic sheet with 800-grit sandpaper until both sides are flat, and spray gold on both sides for 5 min. DC polarize at 140 ℃ and 6 kV / mm for 25 min. Place the polarized sample in an oven and age at 200 ℃ for 12 h to obtain highly uniform manganese-doped BSPT-based piezoelectric ceramic.
2. The method for preparing a highly uniform manganese-doped BSPT-based piezoelectric ceramic according to claim 1, characterized in that, In step S2, the ball milling medium is anhydrous ethanol, the ball milling rate is 200 r / min, and the time is 24 h.
3. The method for preparing a highly uniform manganese-doped BSPT-based piezoelectric ceramic according to claim 1, characterized in that, In step S3, the drying temperature is 110-120 ℃ and the time is 120-140 min.
4. The method for preparing a highly uniform manganese-doped BSPT-based piezoelectric ceramic according to claim 1, characterized in that, In step S4, the calcination process is carried out according to the following procedure: (a) During the heating stage, the temperature was increased from 30 ℃ to 1150 ℃ at a heating rate of 4 ℃ / min, and held for 240 min; (b) During the cooling phase, the temperature is reduced from 1150 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min.
5. The method for preparing a highly uniform manganese-doped BSPT-based piezoelectric ceramic according to claim 1, characterized in that, In step S5, the pre-firing process is as follows: first, the temperature is increased from 30 ℃ to 730-750 ℃ at a heating rate of 4 ℃ / min, and held for 180 min; then, the temperature is decreased from 730-750 ℃ to 30 ℃ at a cooling rate of 4 ℃ / min.
6. The method for preparing a highly uniform manganese-doped BSPT-based piezoelectric ceramic according to claim 1, characterized in that, In step S6, the mass of the added PVA binder is 7 wt.% of the mass of the pre-fired powder.
7. The method for preparing a highly uniform manganese-doped BSPT-based piezoelectric ceramic according to claim 1, characterized in that, In step S7, the sintering process is carried out according to the following procedure: (1) In the first heating stage, the temperature was increased from room temperature to 550 ℃ at a heating rate of 4 ℃ / min, and the temperature was maintained for 120 min for debinding; (2) In the second heating stage, the temperature is increased from 550 ℃ to 900 ℃ at a heating rate of 4 ℃ / min; (3) In the second heating stage, the temperature is increased from 900 ℃ to 1100 ℃ at a heating rate of 2 ℃ / min, and held for 120 min; (4) During the cooling stage, the temperature is reduced from 1100 ℃ to 800 ℃ at a cooling rate of 10 ℃ / min, and held for 180 min. Then, the temperature is cooled to room temperature with the furnace.